HUBUNGAN ANTARA INDEKS PRESTASI DENGAN PENAMPILAN KERJA PERAWAT LULUSAN AKPER PAMENANG PARE DI RSUD. PARE KEDIRI - Nugroho, Christianto (Jurnal AKP, 2010)
The  nurse  job  performance  influenced  by  many  factors,  one  of  them  is  prestation  indeks.  PrestationIndeks  consit  of  general  lecture,  nursing  basic  lecture,  and  profesion  lecture  indeks.These  are  indicated  theirability  about  nursing  science.  But  Nurse  performance  has  not  evaluated  well.  This  research  was    aimed  toinvestigate the influence prestation indeks to nurse job performance in Pare hospital.Design used in this research was cross sectional study. The samples are nurses in Pare Hospital, whograduated from Akper Pamenang. These are 44 respondens, selected with total sampling. The data collected byquisioner and observation then analyzed with SPSS Linier Regretion with Significan level p < 0,05.Results  showed  that  general  lecture  prestation  indeks  had  corelation  with  nurse  job  performance(p=0,005),  profession  basic  lecture  prestation  indeks  had  corelation  with  nurse  job  performance  (p=0.004),profession lecture indeks had corelation with nurse job performance (p=0,003) and comulatif prestation indekshad corelation with nurse job performance (p=0,014).It can be concluded that indeks influenced nurse job performance especially general lecture, profesionbasic lecture and profession lecture prestation indeks. So it will recomended to choose higher prestation indeksinnurse recruitment.